Azerbaijan - Kazimova, Nikki (London : Kuperard ; New York : Distributed in the United States and Canada by Random House, 2011)
Culture Smart! Azerbaijan is an illuminating and practical guide to Azerbaijani culture and society. It will help you turn your visit-whether it's for business or for pleasure-into a memorable and enriching experience. Contents include: Local customs and traditions, the impact of religion, history, and politics, the Azerbaijanis at home, work, and play, eating and drinking, Azerbaijani style, dos, dont's, and taboos, business practices, communication, spoken and unspoken, and many practical tips for managing the unexpected.
Land and people -- Values and attitudes -- Festivals and traditions -- Making friends -- Private and family life -- Time out -- Travel, health, and safety -- Business briefing -- Communication.
"The essential guide to customs and culture"--Cover.
Includes bibliographical references (p. 165) and index.
Keywords: Azerbaijan -- Guidebooks; Azerbaijan -- Civilization; Azerbaijan -- Social life and customs -- 21st century; National characteristics, Azerbaijani; Etiquette -- Azerbaijan